Clinical applications of invasive spinal cord stimulation in neurological disorders: a narrative review - Mengyu He; Yu Tan; Ze He; Shuqin Yu; Chen Zhang; YouQing Deng (Frontiers in Neurology, 2026)
Introduction Invasive spinal cord stimulation (SCS) is used in selected patients with refractory chronic neuropathic pain and has also been explored in spinal cord injury, disorders of consciousness, and Parkinson’s disease. However, the strength of evidence differs substantially across indications. This review summarizes the current clinical applications of invasive SCS and distinguishes relatively established pain indications from emerging neurological applications. Methods We conducted a structured search of PubMed, Embase, the Cochrane Central Register of Controlled Trials, Web of Science, Wanfang, and China National Knowledge Infrastructure. The search was supplemented by reference tracking for landmark studies and a targeted update of relevant publications from 2024 to 2026. Results Randomized evidence is concentrated in chronic pain populations. Conventional SCS has shown benefit in selected patients with failed back surgery syndrome, while 10-kHz SCS produced greater pain reduction than conventional low-frequency stimulation in patients with chronic back and leg pain. Burst stimulation was noninferior to tonic stimulation in the SUNBURST trial and was preferred by most participants. Randomized evidence also supports 10-kHz SCS in refractory painful diabetic neuropathy. Evidence for complex regional pain syndrome suggests short- to intermediate-term pain relief, although long-term benefit remains uncertain. By contrast, applications in diabetic foot complications, spinal cord injury, and disorders of consciousness are supported mainly by small, heterogeneous, or uncontrolled studies. Recent blinded trials have not demonstrated a clear benefit of SCS for Parkinsonian gait impairment. Discussion The clinical evidence supporting invasive SCS varies considerably across neurological indications. Its role is comparatively well supported in selected chronic neuropathic pain populations, particularly chronic back and leg pain after spinal surgery and painful diabetic neuropathy. Evidence for non-pain neurological disorders remains limited, and these applications should remain investigational until further controlled studies clarify patient selection, stimulation parameters, durability of response, and safety.